Paramagnetic magnetization signals and curious metastable behaviour in field-cooled magnetization of a single crystal of superconductor 2H-NbSe2. (8th July 2015) - Kumar, Santosh; Tomy, C V; Balakrishnan, G; Paul, D McK; Grover, A K
Abstract: We present here some newer characteristics pertaining to paramagnetic Meissner effect like response in a single crystal of the low superconducting compound 2H- via a detailed study of effects of perturbation on the field-cooled magnetization response. In the temperature range, where an anomalous paramagnetic magnetization occurs, the field-cooled magnetization response is found to be highly metastable: it displays a curious tendency to switch randomly from a given paramagnetic value to a diamagnetic or to a different paramagnetic value, when the system is perturbed by an impulse of an externally applied ac magnetic field. The new facets revealed in a single crystal of 2H- surprisingly bear a marked resemblance with the characteristics of magnetization behaviour anticipated for the giant vortex states with multiple flux quanta (, , ) predicted to occur in mesoscopic-sized superconducting specimen and possible transitions amongst such states.